ANALYSIS OF FACTORS CAUSING LEARNING DIFFICULTIES AMONG BIOLOGY STUDENTS AT UNIVERSITAS NEGERI MEDAN IN THE ANIMAL DEVELOPMENT COURSE - yossie ulfa nuzalifa; Shofia Lubis; Sailana Mira Rangkuty; Irwana Br Sembiring; Dhini Kamal Ritonga (Jurnal Pelita Pendidikan, 2026)
Animal Development Course is the basic component of the biology study program. Given the importance of Animal Development courses as a basis for understanding advanced concepts in the field of biology, the identification of factors that cause learning difficulties is very important. By understanding these factors, it is hoped that a more effective learning strategy can be developed and in accordance with the needs of students. Based on that background, this research aims to analyze the factors that cause learning difficulties for Biology students at Medan State University in the Animal Development course. This research is expected to contribute to the development of more effective learning strategies and improve the quality of biology education at Medan State University. This research uses a qualitative approach. The instrument used in this study is an interview sheet designed to explore the factors of learning difficulties in depth.